PENGARUH KOMPETENSI DAN IKLIM ORGANISASI SEKOLAH TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Guru di Yayasan Institut Indonesia 48 Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and analyze the effect of Competence andOrganizational Climate on the Performance School Teacher with Job Satisfactionas mediation. Studies on teachers in Indonesian Institute Foundation 48Semarang.Metode used in this study is the sensus method with 95 respondents. Testinstruments used in this study is the validity and reliability, with the criteria KMO> 0.5 , Loading Factor > 0.4 and Cronbach alpha > 0.7 . Normality Test, TestClassical Assumptions used are test heteroscedasticity and multicollinearity test .Test model used is Adjusted R2 ( coefficient of determination ) and F Test(Goodness of Fit) Hypothesis Testing in this study used regression analysis usingt-test, testing the hypothesis on the significance level (α) of 5%. Test mediationusing path analysis.Based on the findings of the research: Competencies positive andsignificant effect on job satisfaction. School Organizational Climate positive andsignificant effect on job satisfaction. Competence positive and significant impacton teacher performance. School Organizational Climate positive and significantimpact on teacher performance. Job Satisfaction and significant positive effect onteacher performance. Job satisfaction does not mediate the effect of the TeacherPerformance Competency. Job satisfaction mediates the influence of the SchoolOrganizational Climate on Teacher Performance.Keywords : Competence , Organizational Climate , Teacher Performance , JobSatisfaction.